Digital Humanitarianism and Global Solidarity: The Role of Indonesian K-Pop Fans in Supporting Gaza - Eka Novita Sari; Ainunia Nur Islami (Indonesian Red Crescent Humanitarian Journal, 2026)
The Al- Aqsa Flood Operation On October 7, 2023, triggered an intense Israeli military response and resulted in genocide in Gaza, with more that 69,000 casualties. This crisis sparked a global wave of soladarity on social media, reflecting a broader shift toward digital Humanitarianism, afrom of tecnology mediated humanitarian practice that enables remote participation in crisis response. This study examines the role of Indonesian K-pop fans in perfoming digital solidarity with Palestine through online campaigns and fundraising initiative in collaboration with local zakat institutions such as Basnaz, Dompet Dhuafa and Rumah Zakat. K-Pop fandom acts as new social agent that bridges popular culture and humanitarianism, forming a transnational philanthopic practice that is locally rooted yet globally impactful. Accordingly, digital humanitarianism can be understood as a social practice that integrates culture, technology, and spirituality, positioning digital solidarity as a new moral expression of youth in confronting contemporary humanitarian crises.